Mediating Role of the Reward Network in the Relationship between the Dopamine Multilocus Genetic Profile and Depression - Gong, Liang; He, Cancan; Yin, Yingying; Wang, Hui; Ye, Qing; Bai, Feng; Yuan, Yonggui; Zhang, Haisan; Lv, Luxian; Zhang, Hongxing; Zhang, Zhijun; Xie, Chunming (Frontiers in Molecular Neuroscience, 2017)
Multiple genetic loci in dopamine-pathway substantially has been associated with depression symptoms in major depressive disorder (MDD). However, neural mechanism underlying the polygenic effects involving in dopamine-pathway on depression remains unclear. We aimed to investigate the neural mechanism underlying the polygenic effects in dopamine pathway on the reward network in MDD using imaging genetic approach. Fifty-three MDD patients and 37 cognitively normal (CN) subject were recruited and completed the resting-state functional MRI scan. Multivariate linear regression analysis was employed to investigate the effects of disease and multilocus genetic profile scores (MGPS) on the reward network, which constructed by nucleus accumbens (NAc) functional connectivity (NAFC) network. DA-MGPS was widely associated within NAFC network, mainly in inferior frontal cortex, insular, hypothalamus, superior temporal gyrus, and occipital cortex. The pattern of DA-MGPS effects in fronto-striatal pathway was opposite in MDD patients compared with CN subjects. More importantly, the NAc-putamen connectivity mediates the association between DA MGPS and anxious depression traits in MDD patients. Our findings suggested that DA multilocus genetic profile makes a considerable contribution to reward network and anxious depression in MDD patients. This finding expands our understanding the pathophysiology of polygenic effects underlying the brain network in MDD patient.